Complete Revascularisation is associated with Improved Survival after Out of Hospital Cardiac Arrest. (14th October 2021) - Kanyal, R; Pareek, N; Sarma, D; Bharucha, A; Dworakowski, R; Melikian, N; Webb, I; Shah, A; MacCarthy, P; Byrne, J
Abstract: Introduction: Coronary artery disease (CAD) is common in patients with Out of Hospital Cardiac Arrest (OOHCA) but the clinical relevance of burden of CAD and evidence for revascularisation strategies in relation to outcomes and modes of death remains unclear. Purpose: This study sought to assess the extent of CAD as defined by the SYNTAX score and prognostic value of complete compared with incomplete revascularisation by evaluating the SYNTAX revascularisation index (SRI) in patients with OOHCA. Methods: 619 patients with OOHCA were admitted at our centre between 1st May 2012 and 31st December 2017. 237 were excluded for having a non-cardiac aetiology or prior neurological disability. 398 patients were included into the study and of these 272 (68.3%) had early coronary angiography (CAG) and were included in the final analysis. The baseline SYNTAX score (bSS) and residual SYNTAX score (rSS) were determined from the coronary angiograms by a cardiologist blinded to the outcome. Patients were subdivided into 4 subgroups according to quartiles of the baseline syntax score (bSS) of 0, Group A: 1–10, Group B: 11–20 and Group C: ≥21. Complete revascularisation (CR) was defined as SRI of 1 and incomplete (IR) as SRI <1 where the SRI=(1-[rSS/bSS]) ×100 (Figure 1). Results: Patients with a bSS of 0 were younger, had less shockable initial arrest rhythms and worse lactate and pH on arrival.Patients with bSS>0 (i.e., those with coronary artery disease) had similar cardiac arrest circumstances in terms of rates of witnessed, bystander CPR and shockable rhythms. Admission metabolic status reflected by pH and lactate and rates of ST elevation/LBBB were also identical for all three groups. However, LVEF on admission decreased significantly as coronary complexity increased (P<0.0001). While early angiography was more preferentially performed in those with higher coronary complexity, paradoxically, those with bSS 1–4 had highest rates of culprit lesions which was reflected in higher rates of PCI (Figure 1). 124 (45.4%) had CR compared with 54.2% with IR. CR was most likely to be achieved as the coronary complexity reduced (Group A – 71.7%, Group B – 41.1%, Group C - 23.3%). There was no difference in rates of cardiogenic shock between both groups (CR 61.1% vs. IR 69% p=ns), but patients with complete revascularisation were younger (58.8 vs 67.8, p<0.0001), lower rates of hypertension and previous CABG (16.2% vs 3.2%, p≤0.0001) CR was associated with decreased mortality at 30 days (45.9% vs 34.6%, p=0.046) and 12 months (49.3% vs 35.4%, p=0.022). The lower mortality rate in CR appeared to partly be driven by lower cardiac deaths though this was not statistically significant (22% vs 7%, p=0.1) (Figure 2). Conclusions: CR in a primary coronary aetiology OOHCA group is associated with reduced early and long-term mortality, which may be driven by a reduction in cardiac deaths. Prospective randomised trials in this population are warranted. FUNDunding Acknowledgement: Type of funding sources: None.